(untitled) (International journal of artificial intelligence, 2025)
This article discusses the issues of promoting HL (HEALTHY LIFESTYLE) through television, radio and social networks, organizing sports events and healthy lifestyle weeks in neighborhoods, the main causes of diseases are physical inactivity, unhealthy diet, tobacco and alcohol consumption, and the fact that supporting HL (HEALTHY LIFESTYLE) for sustainable development is one of the priorities of global health policy.